Measurement of W± and Z0 properties at the CERN Mathematical expressionp collider - Appel, J; Bagnaia, P; Banner, M; Battiston, R; Bernlöhr, K; Borer, K; Borghini, M; Carboni, G; Cavasinni, V; Cenci, P; Chollet, J; Clark, A; et al. (Springer-Verlag, 1986)
A study of W± and Z0 properties has been performed using the UA2 detector at the Mathematical expression collider. The data correspond to a total integrated luminosity of 142 nb-1 at Mathematical expression=546 GeV, and of 310 nb-1 at Mathematical expression=630 GeV. The experimental results are compared with the predictions of the Standard Model of the unified electroweak theory. © 1986 Springer-Verlag.